2021
DOI: 10.3389/fncel.2021.663092
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Invasion in Glioblastoma: Extracellular Matrix, Ca2+ Signaling, and Glutamate

Abstract: Glioblastoma (GBM) is the most common and malignant form of primary brain tumor with a median survival time of 14–16 months in GBM patients. Surgical treatment with chemotherapy and radiotherapy may help increase survival by removing GBM from the brain. However, complete surgical resection to eliminate GBM is almost impossible due to its high invasiveness. When GBM cells migrate to the brain, they interact with various cells, including astrocytes, neurons, endothelial cells, and the extracellular matrix (ECM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 129 publications
2
33
1
Order By: Relevance
“…Axonal growth cone is responsible for determination of cell growth direction, extracellular motility(ECM), and provides growth direction of the axon in that direction(40). Studies have shown that disturbed ECM processes lead to invasion and motility in GBM(41). Since glial cells and axons in GBM lead to aggressive growth which ultimately to lethal tumor formation, could state lack of growth directions from axonal growth cone processes due to the down-regulation of this particular process in GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axonal growth cone is responsible for determination of cell growth direction, extracellular motility(ECM), and provides growth direction of the axon in that direction(40). Studies have shown that disturbed ECM processes lead to invasion and motility in GBM(41). Since glial cells and axons in GBM lead to aggressive growth which ultimately to lethal tumor formation, could state lack of growth directions from axonal growth cone processes due to the down-regulation of this particular process in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Axonal growth cone is responsible for determination of cell growth direction, extracellular motility(ECM), and provides growth direction of the axon in that direction (40). Studies have shown that disturbed ECM processes lead to invasion and motility in GBM (41).Since glial cells and axons in GBM lead to aggressive growth which ultimately to lethal tumor formation, could state lack of growth directions from axonal growth cone processes due to the down-regulation of this particular process in GBM. However investigation of the axonal growth cone pathway in association of GBM could help us gain more insights in progression of this horrendous disease.In association with this, drawing a conclusion to association of beta-amyloid protein binding pathways and it's down-regulation in GBM, here reveal new insights in progression of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Despite much research and clinical investigation in recent years, the prognosis and treatment of glioma are not so desirable ( Xu et al, 2020 ). Great proliferation rate with high resistance to therapies, sensitivity of the CNS and low ability to repair itself, and inability of most drugs to pass the blood brain barrier (BBB) prevent impressive treatment of glioma ( So et al, 2021 ). One of the malignant glioma’s hallmarks is its ability to infiltrate the brain, leads to avoidable recurrence post local therapy ( So et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Great proliferation rate with high resistance to therapies, sensitivity of the CNS and low ability to repair itself, and inability of most drugs to pass the blood brain barrier (BBB) prevent impressive treatment of glioma ( So et al, 2021 ). One of the malignant glioma’s hallmarks is its ability to infiltrate the brain, leads to avoidable recurrence post local therapy ( So et al, 2021 ). Nowadays, existing therapeutic approaches include resection surgery, chemotherapy, radiotherapy, and combination therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is one of the most prevalent and aggressive brain tumors 1 . GBM arises from astrocytes that support nerve cells and invade nearby brain cells 2 . It can affect children; however, it is more common in adults aged 40–75 years 3 .…”
Section: Introductionmentioning
confidence: 99%